2006
DOI: 10.1309/dceqd30v5ueja5gn
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Model of Antigen Retrieval Using a Peptide Array

Abstract: Even though antigen retrieval is highly denaturing, it paradoxically restores immunoreactivity after formalin fixation. It is unclear how this happens. We address this question using a peptide array to model formalin fixation and antigen retrieval. The peptides are linear stretches based on the native protein sequence, containing antibody epitopes of HER-2, estrogen receptor, progesterone receptor, and Ki-67. Of the 7 peptides, 6 retain their immunoreactivity after formalin fixation. However, if formalin fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…348 However, the cross-linking between antigens and unrelated tissue proteins also has a marked effect on the immunoreactivity of antigens after fixation. 347 Cross-linking due to aldehyde fixation can produce new epitopes that specifically react with antibodies designed for another purpose (eg, the specific detection of enamel proteins in glutaraldehyde-fixed tissue by an antibody to vimentin). 178 The basic mechanism of fixation with formaldehyde is the formation of addition products (adducts) between the formalin and uncharged reactive amino groups (-NH or NH 2 ) that eventually will form cross-links.…”
Section: Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…348 However, the cross-linking between antigens and unrelated tissue proteins also has a marked effect on the immunoreactivity of antigens after fixation. 347 Cross-linking due to aldehyde fixation can produce new epitopes that specifically react with antibodies designed for another purpose (eg, the specific detection of enamel proteins in glutaraldehyde-fixed tissue by an antibody to vimentin). 178 The basic mechanism of fixation with formaldehyde is the formation of addition products (adducts) between the formalin and uncharged reactive amino groups (-NH or NH 2 ) that eventually will form cross-links.…”
Section: Fixationmentioning
confidence: 99%
“…412 After an initial drop in immunoreactivity with fixation, there is a plateau of variable duration before antigens become unrecognizable by specific antibodies. 347 Overfixation could produce false-negative results due to excessive cross-links, 142 especially before the advent of heat-based antigen retrieval methods. 205 However, significant reduction of immunoreactivity is detected in only a few markers after several weeks' fixation ( Fig.…”
mentioning
confidence: 99%
“…With respect to the AR technique, several hypotheses pertaining to the mechanism have been proposed (Shi et al 1997;Shi, Gu, Turrens, et al 2000), and recent studies have shed some light Rait, Xu, et al 2004;Sompuram AR et al 2004;Sompuram SR et al 2006;Yamashita 2007). The research group of AFIP (Armed Forces Institute of Pathology), led by Mason, O'Leary, and others, has taken a unique approach to understanding the mechanisms of heat-induced AR.…”
Section: Mechanism Of Armentioning
confidence: 99%
“…Thus, reversal of protein formaldehyde adducts and cross-links are almost certainly fundamental to the success of the AR technique. Bogen, Sompuram, and colleagues conducted similar fundamental work using synthesized peptides as a model system for simulating the loss of immunoreactivity after fixation (Sompuram SR et al 2006;Bogen et al 2009;Bogen and Sompuram 2010). They discovered that most peptide epitopes in isolation did not lose immunoreactivity after treatment with formalin but did lose immunoreactivity if an irrelevant protein was added, possibly blocking the peptide epitope by formaldehyde-induced protein cross-linking.…”
Section: Mechanism Of Armentioning
confidence: 99%
“…Cross-linking of the proteins adjacent to the one carrying the antigen affects the availability of said antigen, 10 and it has been shown that the masking is dependent on the concentration of these bystanders. 11 In an artificial model, the intramolecular bonds are more relevant for masking than the intermolecular bonds, unless fixation occurs in an environment of highly concentrated, macromolecular proteins.…”
Section: Introductionmentioning
confidence: 99%